Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil - Moura, Luciano De A.; Groll, Elisa Von (Zootaxa, 2017)
A catalogue of type specimens of Coleoptera (Insecta) housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul (MCNZ), Porto Alegre, Brazil is presented. The collection contains 519 type specimens (48 primary types and 471 other type specimens), which represent 249 species and 12 families: Buprestidae, Cerambycidae, Chrysomelidae, Ciidae, Cleridae, Curculionidae, Disteniidae, Geotrupidae, Mycteridae, Scarabaeidae, Scraptiidae and Staphylinidae.